DINAMIKA PERKEMBANGAN KURIKULUM PENDIDIKAN: SEBUAH KOMPARASI ANTARA JEPANG DAN INDONESIA - Dwi Purwanti, Mei; HittaA lfi Muhimmah; Nurul Istiq’faroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze and compare the dynamics of curriculum development in both countries. Through analyzing the structure of the Indonesian and Japanese basic education curriculum, it is hoped that it can provide an overview of the structure and implementation of the curriculum in improving the basic education system in Indonesia and draw inspiration from good practices that have proven effective in Japan. The research method used is a literature review with a comparative descriptive study. The data used in this study were obtained from primary and secondary literature sources to obtain information and explanations of previously conducted research. The data obtained is then collected and analyzed, conclusions are drawn and results are obtained regarding the literature study. The analysis revealed similarities and differences in the structure of basic education in Indonesia and Japan. This can be determined from educational policies, learning methods, curriculum structure, and character development included in the curriculum.